(untitled) (AYUSHDHARA, 2023)
Hyperlipidaemia is considered a significant modifiable risk factor for Cardiovascular Diseases (CVD). The risk of cardiovascular events is approximately three times higher in comparison to individuals with normal lipid profile. Current practice of hyperlipidaemia management includes life style modifications, exercise, dietary changes and drug therapy with statins. However, statins are expensive and having several limitations including adverse effects. Hence there has been a long demand for evidence based alternative medicines which can improve lipid profile. It is also one of the thrust areas of WHO to find out economical, safe and effective solutions for non-communicable diseases (NCD) based on traditional medical systems. Ayurveda is the oldest scientific traditional system of medicine practiced in India. It offers a variety of plant based medicines for the management of hyperlipidaemia. The current review is aimed at finding potential medicinal plants for effective management of hyperlipidaemia/dyslipidaemia based on the results of experimental and clinical studies.